HELLP syndrome, a difficult diagnosis: a case report - Pradhan, Shweta; Bhattacharjee, Somen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
HELLP is an acronym that refers to a syndrome characterized by Haemolysis with a microangiopathic blood smear, Elevated Liver enzymes, and a Low Platelet count. Recent studies suggested that some women will develop HELLP without the manifestations of classical symptoms. Authors present the case of a 22-year-old normotensive primigravida who went into severe thrombocytopenia and haemolysis leading to DIC, finally the diagnosis of normotensive HELLP syndrome was made. Present case report attempts to illustrate the diagnostic dilemma that a clinician faces in diagnosing an atypical presentation of HELLP syndrome. Management of jaundice during pregnancy especially in third trimester remains a dilemma for the obstetrician because of its varied aetiology, unpredictable prognosis and guarded perinatal outcome. Authors therefore recommend a rational stepwise approach toward the diagnosis of HELLP syndrome and its atypical presentation.